2002
DOI: 10.1046/j.1365-2672.2002.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of methyl cis-7-oxo deisopropyldehydroabietate on Botrytis cinerea and Lophodermium seditiosum: ultrastructural observations by transmission electron microscopy

Abstract: Aims: To study the antifungal activity of methyl cis-7-oxo-deisopropyldehydroabietate (MCOD) against phytopathogenic fungi, Botrytis cinerea and Lophodermium seditiousm. The effect of the compound was studied by transmission electron microscopy (TEM) and the composition of sterols on both treated and untreated cultures was determined. Methods and Results: MCOD was tested at concentrations in the range 0AE003-0AE5% by the agar plate dilution method. The radial growth of the colonies treated with MCOD was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…All of these alterations result in the plasmolysis of P. fusca cells and ultimately produce the morphological damage visible in conidia (Bélanger et al. 1995; Feio et al. 2002; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these alterations result in the plasmolysis of P. fusca cells and ultimately produce the morphological damage visible in conidia (Bélanger et al. 1995; Feio et al. 2002; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The antagonistic interaction between antifungal compounds and fungal conidia seems to share a common feature, which involves the induction of ultrastructural damages linked to irreversible morphological modifications, all of which result in irreversible damage to conidia, rendering them unviable (Askary et al 1997;Wurms et al 1999;Feio et al 2002;Wang et al 2002). In a previous study, we reported the ability of two strains of B. subtilis, UMAF6614 and UMAF6639, to manage cucurbit powdery mildew disease elicited by P. fusca in in vitro and in planta assays (Romero et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…AbA and its derivatives have recently been evaluated for their ability to function as inhibitors of fungi (5), tumors, mutagenesis, viruses, nitric oxide production (9,12), inflammation (6), and lipoxygenase activity (26). Therefore, enzymes capable of transforming diterpenoids may have potential applications in the synthesis of useful compounds.…”
Section: Resin Is Produced By Most Species Of Coniferous Trees Such Amentioning
confidence: 99%
“…In this work, it was shown that besides abietic acid ( 1 ), CYP106A2 is also able to convert the resin acids isopimaric acid ( 3 ) and dehydroabietic acid ( 2 ), with the spectroscopic data suggesting that the binding modes of the diterpenoids within the active site are quite different. These compounds are of particular interest because they exhibit a wide variety of biological and pharmaceutical properties, such as antimicrobial, antiviral, and antifungal, as well as antitumoral and antimutagenic activities . Because they are well‐represented in the resin of conifers, they are promising candidates for enzymatically catalyzed functionalization with possible enhancement of their biological activities.…”
Section: Discussionmentioning
confidence: 99%